(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The papers provides a theoretical justification of self-regulation on the sociopsychological adaptation of workers, presented the materials research how individual features of sel-regulation infuence on the socio-psychological adaptation of the worker on manuficturing enterprise and its professional effectiveness, are indicative ways and problematic issues for further research.